PERSONAL CHARACTERISTICS OF ATHLETES OF DIFFERENT QUALIFICATIONS (Academicia Globe: Inderscience Research, 2022)
This article discusses the personal characteristics of athletes of various qualifications. The relevance of the study and application of the integration of psychology and sports is revealed. The question is considered that most of the information obtained with the help of personality tests, provided that it is correctly interpreted by competent and professional psychologists, can bring tangible benefits primarily to an individual athlete (sportsmen) than to the entire team as a whole.